Village Resource Development as an Incentive to Sustain the Joint Forest Management Programme - Sethi, Pia; Singh, T. P. (Indian Forester, 2001)
Case studies from India indicate that village resource development activities may provide an important incentive for sustaining interest in the Joint Forest Management Programme apart from leading to improvements in people's livelihood status. Ensuring sustain ability of such activities , however , requires several innovative measures including the development of village funds and enhancing of inter-sectoral linkages.